2020
DOI: 10.1021/acs.jpcb.0c05994
|View full text |Cite
|
Sign up to set email alerts
|

Critical Sequence Hotspots for Binding of Novel Coronavirus to Angiotensin Converter Enzyme as Evaluated by Molecular Simulations

Abstract: The novel coronavirus (nCOV-2019) outbreak has put the world on edge, causing millions of cases and hundreds of thousands of deaths all around the world, as of June 2020, let alone the societal and economic impacts of the crisis. The spike protein of nCOV-2019 resides on the virion’s surface mediating coronavirus entry into host cells by binding its receptor binding domain (RBD) to the host cell surface receptor protein, angiotensin converter enzyme (ACE2). Our goal is to provide a detailed structural mechanis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
93
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(113 citation statements)
references
References 63 publications
20
93
0
Order By: Relevance
“…2d). Similar to the simulations of the RBD-ACE2 complex 12 , the MD simulations of the mutants of the unbound RBD in this work do not show large perturbing effects on the average conformational state. This suggests that while these mutants may have an impact on the stability of the binding interface with ACE2, they do not greatly perturb the conformational state of the RBD in solution and may even serve to reduce the conformational sampling of the unbound RBD.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…2d). Similar to the simulations of the RBD-ACE2 complex 12 , the MD simulations of the mutants of the unbound RBD in this work do not show large perturbing effects on the average conformational state. This suggests that while these mutants may have an impact on the stability of the binding interface with ACE2, they do not greatly perturb the conformational state of the RBD in solution and may even serve to reduce the conformational sampling of the unbound RBD.…”
Section: Discussionsupporting
confidence: 74%
“…It is important to consider how mutations perturb the conformation and dynamics of the RBD, especially during an ongoing pandemic as mutations continue to accumulate 12,13 . Continued identification and evaluation of mutants is crucial in order to better understand the evolving nature of the pandemic, and to ensure that the treatments and vaccines whose primary target is the Spike protein continue to be effective.…”
Section: Analysis Of Spike Protein Mutations Accumulated During the Cmentioning
confidence: 99%
“…While others have performed MD simulations for S RBD-ACE2 or peptides that interact with spike or ACE2 to prevent binding, [25][26][27][28] to our knowledge, MD simulations of both free and bound S RBD for the durations have not been previously reported. These millisecond scale MD simulations provide remarkably strong support for the findings described herein.…”
Section: The Free Spike Receptor Binding Domain Adopts An Optimized mentioning
confidence: 99%
“…1 b) with reported substitutions to G(2) I(7) N(3400) R(2) T(2) X(20), where X denotes any amino acid. Deep mutational scanning of the RBD has shown that a mutation at S477 has a potential to affect the stability of the RBD as well as its binding to hACE2 15 , whereas the structural effect of residue S477 in context of intra-RBD interactions is lesser understood while it is reported that the residues S477 and T478 in SARS-CoV-2 are responsible for specific and efficient interactions with hACE2 and provide an edge over SARS-CoV 16 , 17 . Therefore, we investigate the structural contribution of residue S477 in the RBD in order to understand its role in hACE2 binding.…”
Section: Introductionmentioning
confidence: 99%